The Influence of Sales Promotion on Consumer Purchase Interest in Ud. Samadaya - Tafonao, Aluiwaauri; Waruwu, Yurmanius; Telaumbanua , Setia Murni (Maneggio, 2024)
This study aims to determine the effect of sales promotions on consumer purchasing interest at UD. Samadaya. This research method uses causal quantitative research. This study uses a sample of all consumers who shop at UD. Samadaya. The respondents in this study were all consumers at UD. Samadaya of 70 people. Based on the results of simple linear regression analysis Y = 12.829 + 0.491x. Partially test the hypothesis of sales promotion as an independent variable with a t-count value of 3.134 with a significant level of 0.000 > t-table 1.667. Thus it can be concluded that partially sales promotion influences consumer buying interest at UD. Samadaya. Based on the results of the study, it showed that the t value was 3.134 > 1.667 and a significant level was 0.000 <0.05, meaning that the sales promotion variable (X) had a positive and significant effect on the consumer purchasing interest variable at UD . Samadaya